Analisis Kehidupan Sosial Ekonomi Pengemis dan Penanggulangannya di Kota Banda Aceh - Ulfia Ulfia; Rahmi Rahmi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
This study aims to find out how the socio-economic life of beggars in Banda Aceh and the government's efforts to overcome the problem of beggars in Banda Aceh. This is a descriptive study with a qualitative approach with a sample of 35 beggars. This study used interview in the form of questionnaire surveys and observations field as well as some data from related agencies. The results of the tabulation are illustrated to understand the data obtained from the respondents and the percentage of data analysis. The results showed that the cause of these people became beggars due to several factors that occurred in their lives. The Government has made various efforts to tackle beggars through the Social Service of Banda Aceh in collaboration with the community to eradicate beggars. Efforts that have been made by the Government of Banda Aceh for the prevention of beggars are preventive efforts, coercive efforts, rehabilitation efforts, and social reintegration efforts to prevent the appearance of more beggars. Besides, the efforts to prevent the spread of the effect of begging in the community, the government appeals to the community not to give money and goods to beggars, but they should give them to the social institutions in accordance with the legislation set by the Government of Banda Aceh.